218k views
5 votes
2x - 3y = 1, x + 2y = -3 equivalent equation and solution

User Benhatsor
by
5.9k points

1 Answer

6 votes

Answer:

x = -1, y = -1

Explanation:

Given:


\begin{bmatrix}2x-3y=1\\ x+2y=-3\end{bmatrix}

Solve:


\mathrm{Substitute\:}x=(1+3y)/(2)


\begin{bmatrix}(1+3y)/(2)+2y=-3\end{bmatrix}

Simplify


\begin{bmatrix}(1+7y)/(2)=-3\end{bmatrix}


\mathrm{For\:}x=(1+3y)/(2)


\mathrm{Substitute\:}y=-1


x=(1+3\left(-1\right))/(2)


x=-1


The\:solutions\:to\:the\:system\:of\:equations\:are


x=-1,\:y=-1

Check Answer:

2(-1)-3(-1) = 1

True

-1+2(-1)= -3

True

~Lenvy~

User Utkarsh Srivastav
by
5.2k points